The 39 clues. 2, One false note - Templer, Hannah (39 clues (Graphic novel), 2024)
Amy and Dan find themselves in Vienna, where they search for clues while evading their enemies, and attempt to discover the truth about their famous ancestors, Wolfgang Amadeus Mozart and his sister Nannerl.